Procoagulant Phospholipid Activity and MPV Values in Acute Ischemic Stroke - Cynthia Cynthia; Suzanna Immanuel; Rahajuningsih Dharma Setiabudhy (Indonesian Association of Clinical Pathologist and Medical laboratory, 2024)
Ischemic stroke can be caused by atherothrombosis or embolism. Atherothrombosis occurs due to the rupture of an atherosclerotic plaque causing platelet activation. There are several markers of platelet activation, including platelet microparticles. The levels of platelet microparticles can be measured by examining procoagulant phospholipid (PPL) activity. It is not yet known exactly what activates thrombopoiesis, which can be assessed by an increase in Mean Platelet Volume (MPV). This study aimed to know whether there is an increase in PPL activity and MPV values in acute ischemic stroke, whether platelet activation is influenced by differences in ischemic stroke subtypes, and whether there is a relationship between PPL activity and MPV values in acute ischemic stroke. The study design was cross-sectional and involved 60 subjects. PPL activity in acute ischemic stroke (65.14±13.35 seconds) tends to be higher (shorter clotting time) than in healthy individuals (68.59±8.56 seconds), however, this difference was not statistically and clinically significant. The MPV value in acute ischemic stroke (9.83±0.72 fL) compared to healthy individuals (9.65±0.86 fL) however this difference was not statistically significant. PPL activity in the SAO subtype (61.66±1.31 seconds) tends to be higher than LAA (68.62±14.57 seconds), however, this difference was also not statistically significant. There was a weak correlation between PPL activity (seconds) and MPV value (fL) in acute ischemic stroke (r =0.34, p-value=0.03).